Developing Second Language Speaking Competence through Mobile Learning - Čukatová, Jitka (Univerzita Pardubice, 2018)
This bachelor papers deals with developing second language speaking competences in the context of mobile learning. The aim of my research is to find out what opportunities for development of speaking mobile learning represents. The theoretical part introduces aspects of second language speaking competence. The practical part reveals the outcomes of my classroom research and presents the findings.
Rozvoj mluvení v cizím jazyce prostřednictvím mobilního učení
Keywords: rozvoj mluvení; komunikační strategie; studenti cizího jazyka; mobilní učení; second langauge speaking competence; communication strategies; L2 learners; mobile learning